2007
DOI: 10.12968/bjom.2007.15.8.24393
|View full text |Cite
|
Sign up to set email alerts
|

Delivery suite assessment unit: auditing innovation in maternity triage

Abstract: Delivery suite assessment unit: auditing innovation in maternity triageA Delivery Suite Assessment Unit (DSAU) has been established at a large Northern teaching hospital. This was as a recommendation of ASQUAM (achieving sustainable quality in maternity) to reduce antenatal admissions to delivery suite and provide a more appropriate environment for women attending for antenatal or labour assessment. The DSAU has also provided an effective teaching environment where skills such as effective telephone triage, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…8 The second paper reports on the establishment of a Delivery Suite Assessment Unit in a large teaching hospital in the United Kingdom. 9 The Assessment Unit was established adjacent to the standard delivery suite. The aim of the new unit was to ''reduce antenatal admissions to delivery suite and provide a more appropriate environment for women attending for antenatal or labour assessment'' 9 , p. 506.…”
Section: Background Literaturementioning
confidence: 99%
“…8 The second paper reports on the establishment of a Delivery Suite Assessment Unit in a large teaching hospital in the United Kingdom. 9 The Assessment Unit was established adjacent to the standard delivery suite. The aim of the new unit was to ''reduce antenatal admissions to delivery suite and provide a more appropriate environment for women attending for antenatal or labour assessment'' 9 , p. 506.…”
Section: Background Literaturementioning
confidence: 99%
“…By this point, these women should have been 'booked' in for maternity care and informed about specific midwifery telephone consultation services available in their area. These may be midwifery led telephone consultation based in the community or labour ward areas (Cherry et al, 2009), or specific initiatives designed in local areas (Kennedy, 2007, Cherry et al, 2009, Nolan et al, 2007. Once booked, women should therefore have telephone access to midwives twenty four hours a day (Cherry et al, 2009).…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…In contrast, other studies have shown greater satisfaction and high quality of care with NP consultations, suggesting that there are benefits in expanding the role of NPs within primary care as whole (Seale et al, 2005, Horrocks et al, 2002. The skills required for effective telephone consultation in the health context are considered to be clinical expertise and communication skills essential for a role where no visual cues are available (Purc-Stephenson and Thrasher, 2010) as well as assessing clinical urgency and history taking (Nolan et al, 2007). Although many of these skills are generic, there is no current evidence on whether NPs need specific skills when handling pregnancy related telephone consultations.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations